Combination of Counter Current Salting-Out Homogenous Liquid–Liquid Extraction with Dispersive Liquid–Liquid Microextraction for the High-Performance Liquid Chromatographic Determination of Environmental Estrogens in Water Samples. (4th November 2019) - Shi, Zhihong; Huai, Qingru; Li, Xinye; Ma, Hongyu; Zhou, Can; Chu, Xiaoxue; Zhang, Hongyi
Abstract: In this paper, counter current salting-out homogenous liquid–liquid extraction was combined with dispersive liquid–liquid microextraction for the determination of environmental estrogens in water samples by high-performance liquid chromatography. In this method, initially, sodium chloride was filled into a syringe and a mixture of water sample and acetonitrile was driven to pass through the syringe. Due to salting-out effect, fine droplets of acetonitrile went up through the remaining mixture and aggregated as a separated layer on the top. Then, the collected organic phase (acetonitrile) was removed with a syringe and mixed with carbon tetrachloride (extraction solvent). In the second step, the mixed organic phase was rapidly injected into 5 mL of distilled water to further enrich the analytes. Good linearity was obtained in the concentration range of 2.0~200 ng/mL for diethylstilbestrol (DES) and 8.0~200 ng/mL for octylphenol (OP), respectively. Limits of detection were 0.09 ng/mL for DES and 0.20 ng/mL for OP, respectively. Relative standard deviations for intra- and inter-day precisions were less than 2.1 and 3.1%, respectively. Finally, the established method was successfully applied to determine DES and OP in river water, well water, bottled water and campus drinking water samples with recoveries in the range from 81.0 to 105.9%.